2017
DOI: 10.1159/000477860
|View full text |Cite
|
Sign up to set email alerts
|

Urinary RBP and NGAL Levels are Associated with Nephropathy in Patients with Type 2 Diabetes

Abstract: Background/Aims: The diagnosis of type 2 diabetic nephropathy (T2DN) patients is important to prevent the long-term damaging effects of kidney loss in patients with diabetes and is decisive for patient outcomes. The aim of this study was to explore urine retinol binding protein (RBP) and neutrophil gelatinase-associated lipocalin (NGAL) in T2DN patients with and without albuminuria. Methods: A total of 293 T2DN patients were divided into three groups according to their urine albumin/urine creatinine ratio (UAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
7
19
0
1
Order By: Relevance
“…Studies have shown that urine RBP levels in patients with T2DM are closely related to DN [17,18]. Some studies have shown that urine RBP can be used to assess the degree of renal interstitial brosis due to various causes, progress with ESRD dialysis, and even diabetes related to increased risk of death [19,20]. In this study, we found that urine RBP and MAL levels in the T2DN group were signi cantly increased (P < 0.001).…”
Section: Discussionsupporting
confidence: 48%
“…Studies have shown that urine RBP levels in patients with T2DM are closely related to DN [17,18]. Some studies have shown that urine RBP can be used to assess the degree of renal interstitial brosis due to various causes, progress with ESRD dialysis, and even diabetes related to increased risk of death [19,20]. In this study, we found that urine RBP and MAL levels in the T2DN group were signi cantly increased (P < 0.001).…”
Section: Discussionsupporting
confidence: 48%
“…It seemed that the intensity of its over-expression was linked to neoplasm [20]. Additionally, it has been found that urine NGAL is significantly increased and related to the degree of albuminuria in type 2 diabetic nephropathy (T2DN) [21]. Besides, contrast-induced acute kidney injury (CIAKI) presented with elevations in plasma biomarker of NGAL 24 h after iopromide injection [22].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Among various clinical factors, the major predictor of the development and progression of DN and ESRD is albuminuria [7]. Recently, the list of biomarkers of diabetic nephropathy continues to grow, including not only non-classical protein markers, but also genetic and epigenetic markers [8-10]. Also, intensive research has sought to identify biomarkers of diabetic kidney disease (DKD) progression.…”
Section: Introductionmentioning
confidence: 99%